2012
DOI: 10.1007/s00289-012-0700-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanical and photoluminescence effect of poly(l-lactide) reinforced with functionalized multiwalled carbon nanotubes

Abstract: The poly(L-lactide) (PLLA) biocompatible and biodegradable polymer was reinforced with functionalized Multiwalled carbon nanotubes (MWCNTs) to overcome on insufficient mechanical properties of this polymer for high load bearing applications. To fully realize the potential of MWCNTs for this purpose, they have to be homogeneously dispersed in polymer matrix and have efficient load transfer across the MWCNTs/polymer interface. The pristine MWCNTs (pMWCNTs) were functionalized, at first, by Friedel-Crafts acylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The resonances due to C–CH 3 stretching mode, –CH 3 rocking mode, and –CH 3 asymmetric bending mode of PLA are found in agreement with Refs. at approximately 1080, 1181, and 1454 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 96%
“…The resonances due to C–CH 3 stretching mode, –CH 3 rocking mode, and –CH 3 asymmetric bending mode of PLA are found in agreement with Refs. at approximately 1080, 1181, and 1454 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 96%
“…In order to further analyze their chemical structures, the C1s spectra of CNTs‐COOH, 4PLLA, and CNTs‐ g ‐4PLLA were also studied by XPS. Figure a shows the C1s spectrum of CNTs‐COOH, consisted of four peaks at 284.8, 286.6, 288.7, and 290.0 eV, assigned to CC/CC (73.55%), CO (20.54%), carboxylic CO, and OCO (5.91%), respectively . This indicated that CNTs surface produced a mass of carboxyl groups and hydroxyl groups through acid‐treatment.…”
Section: Resultsmentioning
confidence: 96%
“…The GO-ZnO/PLLA blends were also tested by infrared contrast, and the GO-ZnO/PLLA curves of the blends were found to be different from that of the copolymer ( Figure 5 d), it is consistent with the findings of Sun and He [ 28 ], in which GO-ZnO-PLLA was prepared by the ring-opening polymerization of lactide. Furthermore, the characteristic peaks of PLLA, including the stretching vibration of C–CH 3 , the bending vibration of –CH 3 , and the asymmetric bending vibration of –CH 3 , appeared at 1095, 1187, and 1457 cm −1 , respectively [ 29 , 30 , 31 , 32 , 33 ], in the spectrum of GO-ZnO-PLLA. The results thus show that the PLLA molecular chains were successfully grafted onto the surface of GO-ZnO.…”
Section: Resultsmentioning
confidence: 99%